A solução apresentada por R. M. Hare para os problemas do emotivismo e do descritivismo em filosofia moral - Anselmo Carvalho de Oliveira (Ideas y Valores)
The first part of this article argues that descriptivism as proposed by Moritz Schlick does not correctly understand the function of moral judgements. The second part argues that emotivism does not provide an adequate explanation of the role of reason in ethics. Finally, the article shows how the universal prescriptivism proposed by R. M. Hare furthers the solution of the problems of emotivism, since it extends the role of reason in ethics and in the resolution of the problems of descriptivism, given that it understands the function of moral judgements in ordinary language.